A influência da Indústria Cultural nas preferências musicais de adolescentes do ensino fundamental e médio: estudo de caso - Casagrande, Jaques Luis (2009)
Studies on the cultural industry and its influence on societies marked since the mid - 20th century. The reproduction in series of cultural goods allowed many individuals had access to artistic objects until then restricted to dominant classes. Such processing is seen as positive analysis of some authors however, under other theoretical perspectives this reproduction become cultural consumerization, which undermines the subjectivity, and semiforma populations. The purpose of this study was to examine the field of music education on elementary and middle schools. The methodology adopted was case study. The theoretical foundation is based on Horkheimer and Adorno, in addition to contemporary authors linked to Frankfurt School and to the media studies. As main finding: the option by musical mass production, linked to the paradigms of cultural industry, dominates the scenario and schools contributes to the establishment of such a phenomenon.